An experimental evaluation on thermophysical properties of functionalized graphene nanoplatelets ionanofluids. (November 2018) - Alizadeh, Jalal; Keshavarz Moraveji, Mostafa
Abstract: Ionanofluids (ionic liquid-based nanofluids) as newly introduced types of nanofluids with promising potential for heat transfer and thermal storage applications are created through complex dispersion of ultrafine nanometer-sized particles in ionic liquids. As innovative agents for development of energy sustainability, ionanofluids are widely employed in some applications, i.e., solar panels, catalysts, heat insulators and so forth. Non-flammability and non-volatility features of ionic liquids, make them applicable as green working fluids for any chemical processes. In the present paper, an experimental investigation was conducted on some thermophysical properties (viscosity, electrical conductivity and surface tension) of graphene based ionanofluid as main effective parameters in performance analysis. For this purpose, ionanofluid was prepared at three levels of weight fractions (1%, 2% and 3%) by adding and dispersing polycarboxylate functionalized graphene nanoplatelets (GNPs) in BMIM-PF6 (1-Butyl-3-methylimidazolium hexafluorophosphate) with 98 + % purity as the base fluid. The experimental data was acquired within the temperature range of 293.15 to 333.15 K and at atmospheric pressure (~101 kPa). The results show that the viscosity of ionanofluid decreases with enhancement of temperature and nanoparticle concentration. On the other hand, electrical conductivity of ionanofluid augments as temperature and particle loading increase. For instance, EC at 1% wt. nanoparticles and 303.15 K enhances around 64% compared to the pure IL. Surface tension of the ionanofluids was also determined experimentally as a function of temperature for different mass loadings of nanoparticles. The results reveal that surface tension of ionanofluids decreases slightly as temperature enhances and it reduces with enhancement of nanoparticle fraction as well.